Determination of The Haradness Distribution Pattern Obtained by Nitriding With A Plasma Focus Device - Ng, Chee An (2017)
Plasma focus nitriding is one of the case-hardening which utilizes energetic bombardment of nitrogen ion beam, produced through high temperature due to electrical discharge at high voltage, onto the target material surface. Experiment was carried out by nitriding low carbon steel samples AISI 1020 using different combination of nitrogen pressure (0.5 Torr, 1.0 Torr, 1.5 Ton, 2.0 Torr) and sample distance from anode tip (40 mm, 60 mm, 80 mm, 120 mm) by using UNU/ICTP PFF plasma focus device which was charged initially at 12 kV. Each sample was fired by 30 shots of nitrogen ion beam. The results showed that the plasma focus nitriding produced a localized hardening region near the epicentre of plasma pinch, with diameter ranged between 15 mm – 30 mm. The maximum Vickers microhardness measured was 429.i HV 0.2 at nitrogen pressure of 1.0 Torr and distance from anode o 40 mm. Layering ring-like pattern was observed on the nitrided steel surface . Samples closer to the anode tip (40 mm to 60 mm) exhibited localized rough surface near epicentre, which coincided with the localized hardening region. Radiative Dense Plasma Focus Computation Package (RADPF) software – Lee model code was implemented to generate nitrogen beam related parameters using differential current waveform obtained experimentally. Model fitting and numerical simulation result showed that the optimum plasma focusing in nitrogen environment took place at around 1.0 Torr – 1.5 Torr.